Capacity building for global nursing leaders: challenges and experiences. (3rd October 2016) - Shin, S.; Han, J.; Cha, C.
Abstract : Aim: The aim of this article is to describe our experience in operating a capacity‐building programme, the Korea International Cooperation Project, for global nursing leaders from developing countries, held during the International Council of Nurses (ICN) Conference in 2015 in Seoul, Korea. Background: Globalization points to the importance of global leadership among nursing leaders. In accordance with the theme of 'Global Citizen, Global Nursing' at the ICN conference in 2015, a capacity‐building programme for nursing leaders of developing countries was implemented. Introduction: The global nursing leadership programme shared experiences during the preparation and operation of the conference. To prepare the programme, this paper describes selecting participants, working with invitation lists from 30 countries, and recruiting and training volunteers. The operation of the programme, orientation, organizing tailored programmes for participant groups, addressing unexpected issues and evaluating the programme are described. Implications for nursing policy: ICN could implement capacity‐building programmes for nursing leaders of developing countries during its ICN conference for the nursing society. A programme tailored for each continent with similar sociocultural backgrounds and health issues would provide chances for collaboration and networking. A policy to compile global nursing indicators should be developed. This would allow nursing leaders to learn about the strengths and weaknesses of global nursing and provide evidence for collaboration. Conclusion: The programme was successful in introducing and broadening global perspectives of participants on health and education as well as building a network among leaders and next‐generation leaders in participating countries for future cooperation and collaboration.